Mass-production of high-yield and high-strength thermomechanical pulp fibers from plant residues enabled by ozone pretreatment. (10th May 2021) - Liao, Jianming; He, Shuaiming; Mo, Lihuan; Guo, Shasha; Luan, Pengcheng; Zhang, Xi; Li, Jun
Abstract: Thermomechanical pulp (TMP) has great potential in packaging paper production. However, the lack of raw materials and relatively low physical performance of TMP due to the high lignin content limit its large-scale application. In this study, we use thermomechanical pulping of plant residues combined with ozone treatment to cut costs and improve the physical performance of TMP. During TMP pulping, the effects of the ozone on the structure and physical properties of fibers were investigated. Changing the ozone dosage showed a distinct effect on the surface lignin content and morphology of fibers. In the oxidation process, the structure of lignin was damaged and the physical properties were improved significantly. Moreover, it also proved the feasibility of the mass production of this approach. The fibers of this type have a great future as complementary raw material to recycled fibers to produce packaging paper in applications of paper products of higher quality. Graphical abstract: Image 1 Highlights: The lignin content on the fiber surface reduced after ozone treatment. The physical properties of the TMP were significantly improved by ozone treatment. Energy consumptions declines in the pulping process after ozone treatment. Mass-production of high-quality cellulose fibers from plant residues is possible.